The Relationship Between the Distribution of Water and Salt Elements in Arid Irrigation Areas and Soil Salination Evolution - Lian, Haidong; Sun, Zhaojun; Xu, Cundong; Gu, Fengyou (Frontiers in Earth Science, 2022)
Long periods of surface water irrigation and water and salt movement have slow and continuous influence on the evolution of soil salinization in a closed hydrogeological unit of arid irrigation areas. It is of more application value to study the evolution process of soil salinization from the perspective of regional medium and long terms in the regional scale for the sustainable development of irrigated areas. In this study, the spatial–temporal evolution of soil salinization and dominant factors for soil salination, and the relationship between soil salination and the groundwater buried depth were studied through spatial interpolation and statistical analysis with long-time observed data of a closed hydrogeological unit in the Jingtaichuan Electric-Lifting Irrigation Area in Gansu Province, China. The results showed that from 2001 to 2016, the soil salt content, the groundwater mineralization, and the surface irrigated water amount in the study area enhanced slowly, while the groundwater buried depth decreased; the salinization degree in the study area was increasing slowly; there was a positive correlation between the soil salt content and the groundwater mineralization, while a negative correlation existed between the soil salt content and either the surface irrigated water amount or the groundwater buried depth; the groundwater buried depth had the strongest impact on the spatial distribution of the soil salt content; the increase rate of the soil salt content lowered as the groundwater buried depth increased, which met the logarithmic relationship; soil salination was actively developed in regions with a low groundwater buried depth below 2.5 m, and soil salinization became evident in regions with a groundwater buried depth below 5 m; 15.0 m was a critical groundwater buried depth that caused the increase or the decrease in the soil salt content. The research results provide a new way to predict the development trend of soil salinization in the medium and long terms and provide a theoretical basis for the development of salinization prevention and control measures in irrigated areas, which is of great significance to maintaining a harmonious soil and water environment in irrigated areas.